PEMBELAJARAN KARAKTER DI PERGURURUAN TINGGI ISLAM (Studi Atas Sekolah Tinggi Agama Islam Negeri Pamekasan) - Solichin, Mohammad Muchlis (NUANSA: Jurnal Penelitian Ilmu Sosial dan Keagamaan Islam, 2018)
This writing is trying to understand the character- based teaching and learning in the state of Islamic School Pamekasan. The researcher used qualitative approach in this research, where non-participant observation, interview and documentation as the instrument to collect the data. Data analysis used were data reduction, data display and drawing conclusion.Â  The research resultÂ  showed that the patterns used in the character- based teaching and learning in the State Islamic School Pamekasan are in the form of: 1) uncovering the meaning from several theories, 2) relating the theory analysis with values in life (reflective approach), 3) revealing the siginificance of knowledge, 4) explaining values containing in the knowledge, 5) inserting suggestion for students about self control and keeping away from what is being banned in Islam and social norms, 6) giving some warnings when the students break the rule of ethics, 7) giving punishment to students for breaking the rule.